A comparative study between laparoscopic intraperitoneal onlay mesh hernioplasty and open underlay mesh hernioplasty for ventral hernias - Rao, Adla Satya Narayan; Gupta, Ashwani; Naik, Debasis; Gunasekaran, Gopalakrishnan; Bhandari, Vimal; Rajput, Deepak (International Surgery Journal, 2016)
Background:Even after nearly two decades of experience with laparoscopic ventral hernia repair, there is a surprising paucity of good data clearly proving the benefits of this technique over standard open procedure. The aim of this prospective study was to analyse the surgical technique and perioperative outcomes of laparoscopic intraperitoneal onlay mesh hernioplasty in comparison with the open underlay mesh hernioplasty for ventral hernias. Methods:Sixty patients with ventral hernia included in this study were divided into two groups after randomisation. Study group patients underwent laparoscopic intraperitoneal mesh hernioplasty and control group patients underwent open underlay mesh hernioplasty. Follow-up was done for a period of 6 months and the intraoperative and postoperative outcomes were compared. Results:Patients operated by laparoscopic ventral hernia repair and open underlay mesh hernioplasty were comparable with respect to age, sex, comorbidities, previous history of abdominal surgery, body mass index and size of defect. The laparoscopic approach was associated with shorter operative time, lower blood loss and lesser postoperative pain requiring opioid analgesics for a shorter duration compared to the open approach. Also the length of hospital stay and duration of antibiotic requirement was less with laparoscopic approach. Incidence of seroma and recurrence was lower in the laparoscopic group. Conclusions:Laparoscopic ventral hernia repair although technically demanding, is safe and feasible. It has fewer complications and a better postoperative course, with shorter operative time, less blood loss, lesser postoperative pain, quicker ambulation and shorter duration of hospital stay.